Pengaruh Brand Image Dan Brand Awareness Terhadap Keputusan Pembelian Konsumen (Survei pada Konsumen Lazatto UNSIL di Kota Tasikmalaya) - Farida Safitri; Barin Barlian; Ai Kusmiati Asyiah (Universitas Dehasen Bengkulu, 2024)
This study aims to determine the simultaneous and partial effects of Brand Image and Brand Awareness on Consumer Purchasing Decisions at Lazatto UNSIL Consumers in Tasikmalaya City. the research method used in this research is an associative quantitative method with a survey approach. The population in this study amounted to 100 respondents. The type of data used in this study is primary data obtained through questionnaire data. The data analysis used is multiple linear regression analysis, correlation coefficient, and coefficient of determination. The results of this study indicate that Brand Image and Brand Awareness simultaneously have a significant effect on Consumer Purchasing Decisions at Lazatto UNSIL Consumers in Tasikmalaya City. Brand Image partially, has a significant effect on Consumer Purchasing Decisions at Lazatto UNSIL Consumers in Tasikmalaya City. Brand Awareness partially, has a significant effect on Consumer Purchasing Decisions at Lazatto UNSIL Consumers in Tasikmalaya City.